On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; László, Gyula M. (Zootaxa, 2019)
The identification of the male of Cyana (Cyabarda) torrida (Holland, 1893) is corrected, the male is illustrated for the first time. Cyana suessmuthi Karisch, 2013 is transferred to the subgenus Cyabarda Karisch, 2013, its female adult and female genitalia are illustrated and diagnosed for the first time. A new species Cyana (Cyabarda) nambi sp. nov. similar to C. torrida is described from Uganda. Cyana torrida maculata Karisch, 2013 is upgraded to species rank and transferred to the subgenus Idiovulpecula Karisch, 2013: C. (Idiovulpecula) maculata Karisch, 2013, stat. nov. Two new species of the subgenus Idiovulpecula are described: C. (Idiovulpecula) lowa sp. nov. (Democratic Republic of the Congo) and C. (Idiovulpecula) foya sp. nov. (Liberia). Adults and genitalia of new and related species are illustrated.